2020
DOI: 10.1590/1983-1447.2020.20190334
|View full text |Cite
|
Sign up to set email alerts
|

Risk of pressure injury among users of emergency care units

Abstract: Objective: To identify the risk of pressure injury in patients of emergency care units. Method: Descriptive, cross-sectional, and quantitative by applying the Braden scale to 377 patients from eight units in Paraná, between April and September 2016. Descriptive statistics and Spearman's correlation were used, with a significance of 0.1% for analysis. Results: There was a prevalence of risk-free patients (64.5%; n=243) and of older adults (54.6%; n=206); those at high risk for pressure injury were in the emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
1
0
2
Order By: Relevance
“…Additionally, it has been observed that dependency is associated with increased use of emergency services, a more significant burden for caregivers [ 29 ], and a strong bond with other GSs [ 31 , 32 ], which collectively contributes to a higher risk of adverse health outcomes, including increased short- and long-term mortality, even after the patient has been discharged. In relation to pressure ulcers, it has been observed that this is a parameter that can be used as an early predictor of in-hospital mortality [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been observed that dependency is associated with increased use of emergency services, a more significant burden for caregivers [ 29 ], and a strong bond with other GSs [ 31 , 32 ], which collectively contributes to a higher risk of adverse health outcomes, including increased short- and long-term mortality, even after the patient has been discharged. In relation to pressure ulcers, it has been observed that this is a parameter that can be used as an early predictor of in-hospital mortality [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…(4,6,7) Entre os fatores de risco intrínsecos e extrínsecos para a lesão por pressão, podem-se destacar: idade, uso de drogas vasoativas, estado nutricional, anemia, infecções, sensibilidade cutânea, incontinências, instabilidade hemodinâmica, agitação, umidade, fricção e cisalhamento. (8)(9)(10) Ao identificar os fatores de risco, o profissional deve adotar medidas que diminuam a pressão, a fricção e o cisalhamento na pele sobre as proeminências ósseas, como usar colchões adequados, coxim, reposicionamento de decúbito, coberturas com placa de hidrocoloide extrafino, filme transparente de poliuretano, entre outras. (8,(10)(11)(12) Com o avanço tecnológico, o cuidado prestado ao portador de lesões por pressão vem passando por diversas transformações.…”
unclassified
“…(8)(9)(10) Ao identificar os fatores de risco, o profissional deve adotar medidas que diminuam a pressão, a fricção e o cisalhamento na pele sobre as proeminências ósseas, como usar colchões adequados, coxim, reposicionamento de decúbito, coberturas com placa de hidrocoloide extrafino, filme transparente de poliuretano, entre outras. (8,(10)(11)(12) Com o avanço tecnológico, o cuidado prestado ao portador de lesões por pressão vem passando por diversas transformações. É indiscutível que a introdução da informática e o surgimento de aparelhos sofisticados, como computadores, notebooks, tablets, smartphones e telefones portáteis com internet, trouxeram muitos benefícios, incluindo a rapidez na escolha das coberturas para a prevenção e o tratamento das feridas pelos profissionais envolvidos e o aprimoramento de conhecimentos, permitindo que esses profissionais tenham acesso, em qualquer lugar ou hora, a uma vasta quantidade de informações, tanto do paciente, por meio de seu registro de saúde, quanto das melhores práticas clínicas.…”
unclassified